Black Sea security first. Opportunities and limits in the context of the Montreux Convention - Cristea, Darie; Fîrțală, Valeriu (Technium Social Sciences Journal, 2023)
The Montreux Convention has once again become one of the international normative acts of maximum interest, in the context of the Russian-Ukrainian conflict. The rights and obligations stipulated in the content of this normative act are carefully studied in terms of the effects generated, especially at military, economic and geostrategic level. Protecting the security of the Black Sea area becomes the priority objective, to which decisions on how to implement the provisions of the Montreux Convention also relate, although we are a long way from the moment of signing the Convention, and the architecture of international organization is quite different.